The Influence of Transformational Leadership and Compensation on Employee Performance through Work Motivation - Silvia Hendrayanti; Sari, Cahyani Tunggal (Universitas Negeri Semarang, 2024)
Primadana Yogyakarta Savings and Loans Cooperative has problems with leadership style and compensation which ultimately affects employee performance. It was found that leaders were less familiar with subordinates, leaders were more focused on building relationships with superiors and less focused on subordinates, and employees felt the percentage value of each compensation was getting smaller. The problems that occur require further research to be carried out. The purpose of this research is to determine the direct and indirect influence of Transformational leadership and compensation on employee performance through work motivation at the Yogyakarta Primadana Savings and Loans Cooperative. The population in this study were 62 employees of the Yogyakarta Primadana Savings and Loans Cooperative. The data collection method uses a questionnaire with the data analysis method using the path analysis test with the SPSS application. This research shows that transformational leadership has a positive and significant effect on employee motivation and performance, compensation has a positive and significant effect on employee motivation and performance. Motivation mediates the influence of transformational leadership and compensation on employee performance at the Yogyakarta Primadana Savings and Loans Cooperative. Companies must, through managers/leaders, strive to continue implementing a transformational leadership style and develop work motivation and empowerment for employees, because this has an influence on the performance that will be achieved by company employee.